Carbon Dioxide Hydration Activity of Carbonic Anhydrase: Kinetics of Alkylated Anhydrases B and C from Humans - Khalifah, Raja G. (1972)
A stop-flow kinetic study was performed on the carbon dioxide hydration activity of the human carbonic anhydrase B isoenzyme carboxymethylated at its histidine(200), and of the human C isoenzyme carboxyketoethylated at its histidine(63). The Michaelis-Menten parameters determined between pH 5.6 and 8.7 showed striking differences between the native and the alkylated enzymes, as well as between the modified enzymes themselves. The alkylations caused: (i) a decrease in the k(cat) values, particularly marked for the carboxymethylated B isoenzyme, (ii) a change in the apparent pK of the k(cat) curves, and (iii) a dependence of K(m) on pH, for the alkylated enzymes, in contrast to the pH-independent K(m) values of the native enzymes. The CO(2) hydration and esterase activities of the carboxymethyl B isoenzyme differ markedly in their pH dependence. A kinetic mechanism, which is found to be compatible with all the present observations, is proposed. The results indicate that the modifiable histidine residues do not play an essential role in the catalytic mechanism of the native carbonic anhydrases, but they may well influence the enzyme activity in a secondary role.